2017
DOI: 10.14687/jhs.v14i4.4864
|View full text |Cite
|
Sign up to set email alerts
|

Home advantage in professional soccer: Analysis of Turkey 1. league<p>Profesyonel futbolda ev sahibi olma avantaji: Türkiye 1. liginin analizi

Abstract: In the present study, it was aimed to analyze the home team advantage in 1st Football League of Turkey. Obtained by examining the scores of matches played in 10 seasons (2005/2006-2014/2015), the study data were analyzed in terms of certain technical parameters such as number of games won as home team and guest team, home team advantage by the seasons and teams. The data obtained were entered to SPSS 16.0 software, and the frequency and percentage values were calculated and then interpreted. In totally 3062 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
0
4
0
Order By: Relevance
“…This result is similar to that in amateur leagues. In Turkish First League, home advantage was observed in 61.10% of all matches [20]. The abovementioned results showed that home advantage was a significant advantage for all amateur and professional leagues regardless of the audience.…”
Section: Discussionmentioning
confidence: 67%
“…This result is similar to that in amateur leagues. In Turkish First League, home advantage was observed in 61.10% of all matches [20]. The abovementioned results showed that home advantage was a significant advantage for all amateur and professional leagues regardless of the audience.…”
Section: Discussionmentioning
confidence: 67%
“…In the study examining the home advantage in the Turkish Football 1st League between the 2005-2015 seasons, the average home advantage was found to be 61.10%. In addition, in this study, the average home advantage of the teams that completed a season as champions was found to be 56.40%, while it was determined that this rate was 61.23% for the relegated teams (Gürkan, Göral & Saygın, 2017). In the study conducted in the Turkish Super League in the 2015/2016 season, it was concluded that the ball possession percentages of the teams playing in their own field, their playing time, the number of balls in the attack zone, the number of shots on target, the number of corner kicks and the number of passes from the midfield to the attack zone were higher than the away teams (Gurkan, 2018).…”
Section: Turkish Super League Literature Reviewmentioning
confidence: 67%
“…For the Turkish Super League, Öndes (2019) conducted a study using a point-based calculation to explore the team-specific HA, and it was found to range from Gazi Journal of Physical Education and Sports Sciences, 2024, 29 (2), 61-69 45% to 82.3%. In another study using a similar method, Gürkan et al (2017) found that teams in Turkish 1 st League have a HA ranging from 48.9% to %85.7%. In the studies using the same method used in this study, it was determined that the HA ranged between 56.2% and 81.8% for the individual teams in the Turkish Super League and between 37.9% and 72.9% for the individual teams in the Turkish 1st League, while the AD ranged between 46.7% and 65.4% for the teams in the Turkish Super League and between 46.9% and 73.7% for the teams in the Turkish 1st League (Kuvvetli & Cilengiroglu, 2023, Kuvvetli, 2023.…”
Section: Discussionmentioning
confidence: 98%
“…When considering studies conducted at the team level, in research where HA was examined through point calculation, it was found that the advantage ratio for teams ranged between 45% and 82.3% (Öndes, 2019). In another study employing a similar method, HA for teams in the Turkish 1st League was determined to be between 54.5% and 65.3% (Gürkan, Göral & Saygın, 2017). In studies that investigate HA and AD based on goals scored and conceded by teams, Kuvvetli & Çilengiroğlu (2023) found that the HA for Turkish Super League teams ranged from 56.2% to 81.8%, while the AD ranged from 46.7% to 65.4%.…”
Section: Introductionmentioning
confidence: 99%